Ampicillin plus ceftriaxone therapy against Enterococcus faecalis endocarditis: A case report, guidelines considerations, and literature review. (2022) - Marino, Andrea; Munafò, Antonio; Zagami, Aldo; Ceccarelli, Manuela; Campanella, Edoardo; Cosentino, Federica; Moscatt, Vittoria; Cantarella, Giuseppina; Di Mauro, Rosaria; Bernardini, Renato; Nunnari, Giuseppe; Cacopardo, Bruno
Abstract: Enterococcus faecalis infective endocarditis (EFIE) continues to be a very serious disease, showing considerable morbidity and mortality rates which are influenced by the spread of multi-drug resistant strains occurred in the last decades. Although aminoglycosides were considered the treatment of choice of EIFE, in recent years several studies have investigated alternative therapeutic approaches, including combinations of beta-lactams, mainly because of the aminoglycoside-renowned nephrotoxicity and the widespread development of high-level aminoglycosides resistance (HLAR). In this scenario, we reported a case involving a prosthetic valve infective endocarditis caused by an aminoglycoside-resistant E. faecalis strain which was successfully treated with ampicillin plus ceftriaxone despite the presence of artificial heart valve and the patient's severe clinical conditions.